تعقيد تمزيز النساء في رواية المحبوبات لعالية ممدوح من خلال زمنصزر فقيه - محمد راجي; عبد الباسط (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstract: The novel is a kind of literature that presents a useful value to their readers. Goldmann defines that the novel is a story about the search for the original value and the world believed. While feminist is a group of images of philosophy whose role is to understand the causes of gender and discrimination between men and women, It aims to improve the position of women and give them space to explore abilities in some areas. Feminism is not just theoretical thoughts and images of institutional thought in emptiness, but the feminism is founded on the rights and statistics around women in the world. There are three formulation of the problem in this research. They are how the form of discrimination of women and what are the reasons for the discrimination of women in the novel al-Mahbubat. The purpose of this research was to determine the form of discrimination of women and the cause of female discrimination in the novel al-Mahbubat. This research used descriptive qualitative methods. The result of this research is that the form of female discrimination in the novel is three principally, in terms of position, role, and form of discrimination such as subordination, physical violence, and gender types. While the cause of female discrimination are the individual, the soul of the tempramen, no response from the parties concerned, and do not appreciate. The impact is that women continue to be subjected to abusive treatment, are not respected, have no authority in deciding cases, and are always disregarded. الكلمات الرئسية : الرواية، النسائية، التفريق.